Defining Erosion Limit for Concrete - Luccioni, Bibiana Maria (2013)
Numerical simulation is usually used for predicting the response of concrete and fiber reinforced concrete structures to blast or impact loads. Depending on both charge weight and standoff distance, blast loads can cause fracture and spalling of concrete. In order to numerically reproduce these effects, an erosion model can be used to remove from the calculation the elements that have reached certain criteria. This erosion model represents a numerical tool to avoid great distortion of Lagrange meshes. For this reason, its application to the simulation of a physical phenomenon requires the calibration with experimental results. A review of different erosion criteria and limits used by different authors to simulate concrete under blast loads is presented in this paper. Some application examples and comparisons with experimental results are developed to show the effect of erosion limit on damage results and the dependence on the materials properties, mesh size and scaled distance.